2013
DOI: 10.1002/per.1934
|View full text |Cite
|
Sign up to set email alerts
|

Are Actual and Perceived Intellectual Self–enhancers Evaluated Differently by Social Perceivers?

Abstract: Do actual and perceived self-enhancement entail differing social impressions (i.e. interpersonal evaluations)? Actual self-enhancement represents unduly positive self-views, as gauged by an objective criterion (in this case, IQ scores), whereas perceived self-enhancement involves the extent to which an individual is seen by informants (i.e. peers or observers) as self-enhancing. In an online survey (N = 337), a laboratory experiment (N = 75), and a round-robin study (N = 183), we tested the effects of actual a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 70 publications
(99 reference statements)
0
21
0
Order By: Relevance
“…Dufner et al (2013) reported that the use of self-deception to obtain social benefits is often not guaranteed, but also requires certain self-conditions and social conditions. In daily life, high self-control individuals tend to improve their skills and comprehensive qualities by means of hard study to obtain higher social status and social resources.…”
Section: Discussionmentioning
confidence: 99%
“…Dufner et al (2013) reported that the use of self-deception to obtain social benefits is often not guaranteed, but also requires certain self-conditions and social conditions. In daily life, high self-control individuals tend to improve their skills and comprehensive qualities by means of hard study to obtain higher social status and social resources.…”
Section: Discussionmentioning
confidence: 99%
“…For example, compared to low self-enhancers, high self-enhancers are liked less by well-acquainted peers (Paulhus, 1998). Similarly, people who overestimate their status in a group are liked little by the other group members (Anderson, Ames, & Gosling, 2008) (but see Dufner et al, 2013;Taylor, Lerner, Sherman, Sage, & McDowell, 2003a).…”
Section: Christian Self-enhancement 72mentioning
confidence: 99%
“…And low‐to‐moderate confidence (cf. self‐enhancement) is more socially attractive than overconfidence (Dufner et al., ). These considerations agree with the Aristotelian idea that virtue results from a balance between excess and deficiency (e.g., Grant & Schwartz, ; Imhoff & Koch, ).…”
Section: Introductionmentioning
confidence: 99%